Logistics service providers and Industry 4.0: A systematic literature review - Ricardo Moreira da Silva; Guilherme F. Frederico; Jose Arturo Garza-Reyes (Logistics, 2023)
Background: Industry 4.0 is one of the topics related to manufacturing, supply chain and logistics that has received great interest from the academic community, organizations and governments in the last decade. Problem statement: Several published articles discuss and seek to conceptualize what the fourth industrial revolution is, but no research relates Industry 4.0 in the context of logistics service providers (LSPs) in a clear and structured way. Objectives: This study aims to fill this research gap, proposing a conceptual framework and addressing the challenges, barriers and organizational dimensions that need adaptation to insert LSPs in the new Industry 4.0 environment. Methods: This theoretical and conceptual study uses the Systematic Literature Review (SLR) as a research method to understand the Industry 4.0 phenomenon in the context of LSPs. Contributions: The relevant constructs identified in this research will help professionals and organizations that provide logistics services to develop strategies and encourage new research in the field of Industry 4.0 from the perspective of LSPs. Results: In addition, this research identified and generally consolidated six dimensions, as a result of this innovative study a conceptual framework is presented.
Keywords: 650; 3PL/4PL; Industry 4.0; Logistics 4.0; logistics service providers; Supply Chain 4.0; systematic literature review